Sex differences in type 2 diabetes - Kautzky-Willer, Alexandra; Leutner, Michael; Harreiter, Jürgen (Diabetologia, 2023)
The prevalence of type 2 diabetes mellitus is increasing in both sexes, but men are usually diagnosed at a younger age and lower body fat mass than women. Worldwide, an estimated 17.7 million more men than women have diabetes mellitus. Women appear to bear a greater risk factor burden at the time of their type 2 diabetes diagnosis, especially obesity. Moreover, psychosocial stress might play a more prominent role in diabetes risk in women. Across their lifespan, women experience greater hormone fluctuations and body changes due to reproductive factors than men. Pregnancies can unmask pre-existing metabolic abnormalities, resulting in the diagnosis of gestational diabetes, which appears to be the most prominent risk factor for progression to type 2 diabetes in women. Additionally, menopause increases women’s cardiometabolic risk profile. Due to the progressive rise in obesity, there is a global increase in women with pregestational type 2 diabetes, often with inadequate preconceptual care. There are differences between men and women regarding type 2 diabetes and other cardiovascular risk factors with respect to comorbidities, the manifestation of complications and the initiation of and adherence to therapy. Women with type 2 diabetes show greater relative risk of CVD and mortality than men. Moreover, young women with type 2 diabetes are currently less likely than men to receive the treatment and CVD risk reduction recommended by guidelines. Current medical recommendations do not provide information on sex-specific or gender-sensitive prevention strategies and management. Thus, more research on sex differences, including the underlying mechanisms, is necessary to increase the evidence in the future. Nonetheless, intensified efforts to screen for glucose metabolism disorders and other cardiovascular risk factors, as well as the early establishment of prophylactic measures and aggressive risk management strategies, are still required for both men and women at increased risk of type 2 diabetes. In this narrative review we aim to summarise sex-specific clinical features and differences between women and men with type 2 diabetes into risk factors, screening, diagnosis, complications and treatment. Graphical abstract